ORAL AND DENTAL CARE SEEKING BEHAVIOUR AMONG ELDERLY PATIENTS WITH DIABETES MELLITUS IN INDONESIA - Wisnu Fadila; Riza Fatma Arifa (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
Elderly patients with diabetes mellitus (DM) are susceptible to oral health problems. These issues may affect their oral health-related quality of life (OHR-QoL) such as speaking, eating, and other routines. Therefore, this type of patient needs to seek oral and dental care (ODC). This study examines the sociodemographic facets of ODC-seeking behavior among elderly DM patients in Indonesia by analyzing the 2021 Indonesia Healthcare and Social Security Agency (IHSSA) secondary dataset on first-level healthcare facility visits. This study's samples included 55,291 elderly patients aged 60 years and over, and 634,730 visits to FKTP overall. The analysis was conducted using percentages and cross-tabulations. The study finds that the proportion of ODC visits at the national level is extremely low (1.1%) and the proportion of patients who have oral health complications is likewise (6.6%). It appears that DM patients aged 60-69 (77.8%), male patients (78.6%), single patients (78%), and IHSS non-subsidy members (78.5%) are more likely to seek out ODC than their counterparts. The majority of DM patients have pulp and periapical diseases (46.5%), followed by gingival and periodontal diseases (20.3%), and dental caries (11.8%). There are also disparities among those variables on a regional level. Our study highlights the necessity of preventive action to minimize oral health problems and enhance OHR-QoL among elderly DM patients in Indonesia, by improving oral health education and regular oral examinations.